Service Innovation Strategies in Healthcare: A Case Study of Clinic Skin Care Business - Putri, Octaviani Surya; Dellyana, Dina (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
The global beauty and aesthetic industry has experienced remarkable growth, driven by rising consumer consciousness towards self-care and wellness. In Indonesia, the skincare and aesthetic services market has evolved significantly, with the medical aesthetics market reaching USD 257.05 million in 2023 and projected to grow to USD 495.64 million by 2029. This study explores service innovation strategies in healthcare, specifically within the context of Clinic Skin Care X, an aesthetic clinic in Bandung. The research focused on identifying service quality gaps using the SERVQUAL model and developing practical service innovations to address these gaps. Using a mixed-methods approach, data was collected from 85 patients through structured questionnaires based on the SERVQUAL framework. The analysis revealed that Clinic X generally meets or exceeds customer expectations, with the Empathy dimension recording a positive gap (+0.244). However, the Reliability dimension showed the largest negative gap (-0.938), signaling challenges in consistently meeting promises regarding consultation punctuality and pharmacy services. Based on these findings, strategic service innovations were proposed, including digital queue management systems, mobile app notifications, enhanced staff communication training, and workflow improvements. The study concludes that prioritizing the Reliability dimension through systematic digital transformation and staff empowerment can significantly enhance patient satisfaction and establish sustainable competitive advantage in the aesthetic clinic market.